Data protectionism. - Lane, Patrick (Economist)
The article focuses on data protectionism with the advent of cloud computing. Topics include the global company spending on public cloud services between 2011 and 2014, the concern over data surveillance, and the technical restraints of cloud computing security. Information is provided on data protection laws and the legacy left by whistleblower Edward Snowden.